Validity and reliability of methods for testing vertical jumping performance - Hatze, H. (Journal of Applied Biomechanics, 1998)
The validity and reliability of the jumping ergometer method for evaluating performance in two-legged vertical countermovement and serial rebound jumps were investigated. The internal segmental and nonvertical energy flow components for drop jumps were also studied. The exact dynamic equations governing the jumping motion in three dimensions were derived and used together with the approximate relations of the jumping ergometer method to evaluate a total of 72 vertical jumps of different types executed by 22 subjects (15 males, 7 females), average age 24.59 years. The force-plate method was selected as a reference procedure, to which the jumping ergometer results were related. For countermovement jumps, the relative error for jumping height was 3.55% (±2.92%), and for average power per kilogram body mass during the propulsion phase it was 23.79% (±4.85%). For serial rebound jumps, the respective errors were 7.40% (±4.58%) and 5.09% (±4.48%). Internal and nonvertical energy flow components amounted to about 3% of the total. It was concluded that, because of a number of invalid assumptions, unpredictable errors, and contradictory performance requirements, the validity and reliability of the jumping ergometer method for evaluating certain aspects of athletic performance are highly questionable. D